François Mauriac revisited - O'Connell, David (Twayne's world authors series, 1995)
Observing that Mauriac's "influence at home and abroad was enormous during his lifetime" and that "since his death, no 'Catholic writer' of comparable stature has emerged to replace him," O'Connell underscores Mauriac's enduring place in world literature. Readers seeking a first-rate guide to this cardinal writer need look no further than Francois Mauriac Revisited